The effect of gamification on students’ motivation in learning English - Anisa, Khairani Dian; Marmanto, Sri; Supriyadi, Slamet (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2020)
Motivation plays important role that drives learning. The application of games for educational purposes can boost students’ motivation. Nowadays, the game utilizes technology which enables students to experience enjoyment in a more accessible way. However, some games are not suitable for students. Hence, gamification, i.e., the implementation of game elements in a non-game context, serves as a solution to motivate students. This study aims to investigate the effect of gamification on students’ motivation in learning English. A game-based student response (GBSR) is an example of gamification. The case study method comprised an intrinsic and extrinsic motivation scale and a semi-structured interview to investigate the effect of gamification on students’ motivation in learning English. The study involved 13 eleventh grade students consisting of 10 females and 3 males students. The result indicated that the students experienced competence, autonomy, and relatedness in GBSR which led to stronger intrinsic learning motivation. Besides, the features in the GBSR triggered students’ interest to play the game. The extrinsic motivation stimulated through the reward structure and endorsement of goals. Moreover, the classroom atmosphere became more enjoyable for students. These results serve an alternative way for teachers to teach English at the secondary level.